Between Prometheus and Epimetheus; the role of supervision in a diverse and changing context - Fernández Enguita, Mariano (Avances en Supervisión Educativa, 2014)
No matter that bibliography on the functions of educational supervision rarely forgets to mention the trilogy control-assessment-mentoring, the professional collective looks always divided between its roles as control device or as avant-garde, i.e. on its interventions ex ante and ex post. But its real role is more related to a peculiar response to the problem of the span of control in a loosely coupled system in which a professional group very jealous about its own autonomy dominates organizations. And its future, in the context of informational society, could be finally more related with a posteriori assessment and accountability than with a priori guidance and counseling; that is, it could be more Epimethean than Promethean, and for good.